Isatin Derivatives as Human Intestinal Carboxylesterase Inhibitors: An Approach towards 3D-QSAR, Pharmacophore and Molecular Docking - Sanmati K. Jain; Piyush Ghode; Achal Mishra (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Carboxylesterases (CEs) metabolize numeral drugs and their inhibitions extend the bioactivity or may decrease the harmfulness of compounds that are triggered by these enzymes. Isatin derivatives which were reported as carboxylesterase inhibitors selected in order to establish structure activity relationship quantitatively by using k-nearest neighbour molecular field analysis (kNN MFA). The dataset comprised of 49 compounds and sphere exclusion (SE) algorithm was applied for the division of the data set into training and test set. The models were generated using different values of dissimilarity levels, of which, the best model was obtained (dissimilarity value 3.75) showed cross validated correlation coefficient (q2) 0.8594 and predicted correlation (pred_r2) 0.8106 with test set of 9 compounds. kNN-MFA methodology with stepwise (SW) forward-backward, was used for building the QSAR models. The kNN-MFA contour plots showed relationship between structural features of substituted isatin derivatives and their activities which may be used to design newer potential CE inhibitors. Pharmacophore studies reveals common two aromatic (AroC) and two hydrogen bond acceptors (HAc) features obtained from Molsign and Pharmagist approaches. The present work may be useful for further lead optimization and designing of potent carboxylesterase inhibitors. Molecular docking study was performed to identify potential interactions of the compounds with carboxylesterase active site. For this purpose the pdb id 2hrq (crystal structure of human carboxylesterase with soman) was chosen. Compound 62 exhibits a comparable docking score and bind into the active site of enzyme.